Role of matrix metalloproteinases in diabetic foot ulcers: Potential therapeutic targets - Fu, Kang; Zheng, Xueyao; Chen, Yuhan; Wu, Liuying; Yang, Zhiming; Chen, Xu; Song, Wei (Frontiers in Pharmacology, 2022)
Diabetic foot ulcers (DFUs) are pathological states of tissue destruction of the foot or lower extremity in diabetic patients and are one of the serious chronic complications of diabetes mellitus. Matrix metalloproteinases (MMPs) serve crucial roles in both pathogenesis and wound healing. The primary functions of MMPs are degradation, which involves removing the disrupted extracellular matrix (ECM) during the inflammatory phase, facilitating angiogenesis and cell migration during the proliferation phase, and contracting and rebuilding the tissue during the remodeling phase. Overexpression of MMPs is a feature of DFUs. The upregulated MMPs in DFUs can cause excessive tissue degradation and impaired wound healing. Regulation of MMP levels in wounds could promote wound healing in DFUs. In this review, we talk about the roles of MMPs in DFUs and list potential methods to prevent MMPs from behaving in a manner detrimental to wound healing in DFUs.